Pengaruh Penggunaan Pasir Pulau Bungin Kabupaten Kuantan Singingi Pada Campuran Laston Lapis Aus - Kairon Wika Rejeki Sembiring; Sri Djuniati; Gunawan Wibisono (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Sand of Pulau Island Bungin is a natural sand that comes from Batang Kuantan River, Koto Taluk Kuantan Village, District Kuantan Tengah, Kuantan Singingi Regency, Riau Province. The availability of natural sand makes progress of Kuantan Singingi regency because it is easily obtained and more economical do not need to bring sand material from other area and do not have to go through stone breaking process by stone crusher. Based on the a general Specification Bina Marga 2010 Revision 3, the use of natural sand for asphalt concrete mixture (AC) should not exceed 15% of the total aggregate mixture weight. Therefore, we need to know the efficiency of natural sand usage in asphalt concrete mix (AC) for optimal utilization. This study aims to find out how optimum asphalt (KAO) and to know Marshall characteristics whether to meet the General Specification of Bina Marga 2010 Revision 3. The fine aggregate variation of natural sand used in this research is 0%, 5%, 10%, 15%, 20 % Of the total weight of the aggregate mixture. The addition of natural sand in the asphalt concrete wearing course (AC-WC) causes the value of optimum asphalt (KAO) to decrease. In the mixed asphalt concrete wearing course (AC-WC), the addition of 10% saturated sand obtained an optimum asphalt (KAO) value of 6,10% and the largest stability value of 1.343 kg. If without considering the limits of natural sand usage as set out in Specification of Bina Marga 2010 Revision 3 then the natural addition of sand may still be used in asphalt concrete wearing course (AC-WC) until 20%.Keywords: Natural sand, mixed asphalt concrete wearing course (AC-WC), characteristics of Marshall and a general Specification Bina Marga 2010 Revision 3.